Beneficial Outcomes of Omega-6 and Omega-3 Polyunsaturated Fatty Acids on Human Health: An Update for 2021 - Djuricic, Ivana (Nutrients, 2021)
Oxidative stress and inflammation have been recognized as important contributors to the risk of chronic non-communicable diseases. Polyunsaturated fatty acids (PUFAs) may regulate the antioxidant signaling pathway and modulate inflammatory processes. They also influence hepatic lipid metabolism and physiological responses of other organs, including the heart. Longitudinal prospective cohort studies demonstrate that there is an association between moderate intake of the omega-6 PUFA linoleic acid and lower risk of cardiovascular diseases (CVDs), most likely as a result of lower blood cholesterol concentration. Current evidence suggests that increasing intake of arachidonic acid (up to 1500 mg/day) has no adverse effect on platelet aggregation and blood clotting, immune function and markers of inflammation, but may benefit muscle and cognitive performance. Many studies show that higher intakes of omega-3 PUFAs, especially eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), are associated with a lower incidence of chronic diseases characterized by elevated inflammation, including CVDs. This is because of the multiple molecular and cellular actions of EPA and DHA. Intervention trials using EPA + DHA indicate benefit on CVD mortality and a significant inverse linear dose–response relationship has been found between EPA + DHA intake and CVD outcomes. In addition to their antioxidant and anti-inflammatory roles, omega-3 fatty acids are considered to regulate platelet homeostasis and lower risk of thrombosis, which together indicate their potential use in COVID-19 therapy.